Update on Clinical Trial EMA – SPK: Everolimus verus Mycophenolic Acid in Simultaneous Pancreas and Kidney Transplantation to Evaluate the Differencies in Retinal Neovascularisation in Patients with Diabetic Retinopathy. (July 2018) - Voglova, Barbora; Zahradnicka, Martina; Nemetova, Lenka; Vicanyova, Jana; Kesslerova, Katerina; Sosna, Tomas; Saudek, Frantisek
Background: Patients with type 1 diabetes (T1D), treated with simultaneous pancreas and kidney transplantation (SPK), commonly have advanced stages of diabetic retinopathy (DR). New therapeutic agents targeting the production of proangiogenic signalling pathways in the in retina have been tested in experiments, including local mTOR inhibitors application. We initiated a randomized clinical trial to evaluate the role of systemic mTOR inhibition after SPK in the course of DR. Methods: Main objective is a complex ophthalmological endpoint (grade and progression of the DR, new indication to laser therapy, clinically significant macular edema, visual acuity, cataract grade, central macular thickness, intravitreal bleeding and neovascularisation). Secondary endpoints are patient and graft survival, graft function, wound healing and complications. We include patients with T1D on the waiting list for SPK and randomize them to treatment with natrium mycophenolate (1440 mg/day) or everolimus (through concentration 4–8 ng/l). All receive tacrolimus, induction with antithymocyte globulin and short-term steroid treatment. Complete eye examination including optical coherence tomography is done at baseline, 6, 12 and 24 months post-transplant. We performed an updated analysis of our data for secondary endpoints. Results: After three years 47 patients (out of 50 enrolled) have undergone successful SPK, 14 have successfully completed the 2 years, 25 have completed 1 year follow up. Our data show comparable patient and graft survival and long term kidney function. There was a higher incidence of biopsy proven kidney graft rejections (mostly in the cathegory of borderline changes) and pancreas graft rejections, but neither of them statistically significant, in the group treated with everolimus. We also observed significantly higher glycated haemoglobin levels in the everolimus-treated group, however with slightly higher levels of both fasting and stimulated C-peptide throughout all the follow-up period. In the early postoperative period, the rate of serious complications with need for surgical revision and the time to wound healing did not differ between the two groups. Nevertheless, in the longer follow up, significantly higher number of subjects in the everolimus-treated group developed hernias requring surgical treatment. In the mycophenolate-treated group we have seen higher incidence of severe leucopenias and neutropenias and recurring urinary tract infections. Other complications (i.e. tremor, diabetic foot ulcers, viral infections, diarrhoea, progression of ischaemic heart disease, rash and others) did not differ significantly between the compared groups. Conclusion: Assessment of the preliminary data for secondary endpoints shows results in accordance with previous findings. Ophthalmological endpoints will be evaluated when sufficient amount of data allows a valid statistical analysis. Study is open for new participants. Ministry of Health of the Czech Republic, grant number 15–26746 A.